Asuhan Keperawatan Klien Dengan Benigna Prostat Hyperplasia Post Prostatectomy di Ruang Flamboyan RSUD Pandan Arang Boyolali - Damayanti, Vita; , Arina Maliya, S.Kep., M.Si.Med (2015)
Background: benigna prostat hyperplacia often found in men aged 50 years and sugery is an option appropriate action within its management, the incidence and nursing problems that arise in the client Benigna Prostat Hyperplacia very commonly found in Indonesia. Aim of Research: to study about nursing care on client Mr.S with Benigna Prostat Hyperplacia including assesment, intervention, implementation and evaluation nursing. Result: reduced pain scale 2, overcome barriers to physical mobility, client is able to move the muscles and joints, client looks relax, knowledge of the signs of infection increases. Conclusion: Team work between client and family and care giver was absoluty needed, with relaxation techniques, train Range of Motion on client, sterile wound care principles, a diet high in fiber and protein, education/motivation can overcome the problem of client. Key words: Benigna Prostat Hyperplacia, Post Operation Open Prostatectomy.